Symptom or Culprit? Social Media, Air Pollution, and Violence - Xinming Du (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper provides the first causal evidence that hostile activities online lead to physical violence. Given the recently documented relationship between pollution and social media, I exploit exogenous variation in local air quality as the first step to instrument for online aggression. In an event study setting, I find volatile organic compounds (VOCs) increase by 7% when refineries experience unexpected production outages. Together with higher air pollution, I find more aggressive behaviors both online and offline, as well as worse health outcomes near refineries. A one standard deviation increase in surrounding VOCs leads to 0.16 more hate crimes against Black people and 0.23 more hospital visits per thousand people each day. Second, I consider how emotional contagion spreads through social networks. On days with pollution spikes, surrounding areas see 30% more offensive and racist tweets and 12% more crimes; those geographically distant but socially networked regions also see offensive and racist tweets increase by 3% and more crimes by 4.5%. Nationally, overlooking spillovers would underestimate crime effects of pollution by 24%. My findings highlight the consequences of social media hostility and contribute to the public debate on cyberspace regulation.
Keywords: 330; Luftverschmutzung; Gewalt; Social Web; Kausalanalyse; USA